2020
DOI: 10.1186/s13018-020-02093-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the corrective contribution of strong halo-femoral traction in the treatment of severe rigid nonidiopathic scoliosis

Abstract: Introduction Strong halo-femoral traction has been widely used in the field of severe rigid scoliosis correction. The objective of this study was to analyze the corrective contribution of strong halo-femoral traction in the treatment of severe rigid nonidiopathic scoliosis and discuss its meaning. Material and methods A retrospective review was performed for patients with severe rigid nonidiopathic scoliosis who were treated with halo-femoral traction in our center from December 2008 to December 2015. All cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Regarding the surgical strategy for severe NMS, anterior release and posterior fusion surgery, intraoperative halo-femoral traction, and preoperative halo-gravity traction have been reported to be effective in severe scoliosis surgery, including NMS and idiopathic scoliosis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Auerbach et al reported that good PO correction in patients with NMS with larger and less flexible curves could be achieved using anterior release and posterior fusion surgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the surgical strategy for severe NMS, anterior release and posterior fusion surgery, intraoperative halo-femoral traction, and preoperative halo-gravity traction have been reported to be effective in severe scoliosis surgery, including NMS and idiopathic scoliosis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Auerbach et al reported that good PO correction in patients with NMS with larger and less flexible curves could be achieved using anterior release and posterior fusion surgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allogenous or autogenous bone grafts were implanted for fusion. 8,9 Statistics Analysis Normality of all data was proved using SPSS 22.0 (IBM) (Supplementary Table 1, http://links.lww.com/JAAOS/ A762). Sample size power analysis was performed using PASS 2021 (NCSS Statistical Software) (Supplementary Table 2, http://links.lww.com/JAAOS/A762).…”
Section: Traction Protocolmentioning
confidence: 99%
“…All protocols were described in our previous studies. 8,9 Surgical Procedure During the operation, heavy HFT was maintained, and intraoperative neurophysiologic monitoring was used to carefully monitor spinal cord function. Posterior-column osteotomies were performed to correct the spinal deformity, including pedicle screw placement, release of rigid structure (facet joint, intertransverse ligaments, and softtissue contractures), distraction, compression, rod rotation, and derotation.…”
Section: Traction Protocolmentioning
confidence: 99%